2007
DOI: 10.1016/j.jas.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of XRF and PXRF for analysis of archaeological obsidian from southern Perú

Abstract: Chemical sourcing is becoming an increasingly important component of archaeological investigation. Instruments used for elemental analysis generally must be operated in a controlled laboratory environment. Further, many methods require destruction of a small portion of the objects under investigation. These facts inhibit the application of chemical sourcing studies in a number of research contexts. Use of portable nondestructive instruments would resolve these issues. Sixty-eight obsidian artifacts from the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 47 publications
3
105
0
6
Order By: Relevance
“…The vertical complementary model has been the subject of much discussion in the Andes (Aldenderfer 1993;Masuda et al 1985;Van Buren 1996), with related models proposed such as the "altiplano mode" of integration which proposes extensive networks based on trade in the (Browman 1981(Browman , 1990). In support of Browman's "altiplano mode," regional distributions of Chivay obsidian appear to be confined to middle-and high-altitude sites throughout Andean prehistory (Burger et al 2000;Craig et al 2007;Frye et al 1998;Giesso 2000;Tripcevich 2007: 183-191).…”
Section: Regionmentioning
confidence: 98%
“…The vertical complementary model has been the subject of much discussion in the Andes (Aldenderfer 1993;Masuda et al 1985;Van Buren 1996), with related models proposed such as the "altiplano mode" of integration which proposes extensive networks based on trade in the (Browman 1981(Browman , 1990). In support of Browman's "altiplano mode," regional distributions of Chivay obsidian appear to be confined to middle-and high-altitude sites throughout Andean prehistory (Burger et al 2000;Craig et al 2007;Frye et al 1998;Giesso 2000;Tripcevich 2007: 183-191).…”
Section: Regionmentioning
confidence: 98%
“…Energy dispersive X-ray fluorescence (ED-XRF) has since been established, and hand-held models of XRF have become a preferred instrument for being portable, non-destructive, and increasingly, trace element detection abilities. pXRF and lab XRF have been compared (Craig et al, 2007), and recently pXRF analyses have been integrated with analyses using other instruments and methodologies (Orange et al, 2017). The literature on pXRF and obsidian is vast, and suffices here to say that the instrument has sufficient detection abilities to discriminate among sources and subsources within a continental area, with some current instruments achieving high levels of precision (Tykot, 2016).…”
Section: Stratigraphicmentioning
confidence: 99%
“…[99][100][101][102] All discuss the feasibility of mobile instrumentation compared to traditional laboratory-based XRF and alternative techniques such as instrumental neutron activation analysis for achieving the high accuracy required for obsidian sourcing. Quantitation approaches included linear regression, 101 quadratic regression, 99 fundamental parameters, 100 and corrections utilizing Compton scatter. 102 And while the researchers all concluded that mobile XRF can be successfully used for obsidian sourcing, concerns were noted by some.…”
Section: Spectroscopic Analysismentioning
confidence: 99%